Behavior of Participating Leadership in Developing Job Satisfaction of Islamic Religious Teachers in Private Vocational School in Jambi - Hairul Fauzi; Muntholib Muntholib; Kasful Anwar Us (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2021)
This paper recognized and provided an overview of participatory leadership efforts in developing lecturer job satisfaction. A qualitative approach allows us to know the subject more directly and intimately. Data collection methods include observation, interviews, and documentation. The Miles and Hubermen model was used to analyze the data used in this analysis. Based on the report, the following conclusions can be drawn 1) make decisions with the help of subordinates; 2) The leadership of PTKIS empowers lecturers by holding training activities, seminars, workshops, making resource persons in campus activities, assigning tasks and responsibilities based on their expertise and educational background, recommending lecturers to continue their doctoral degrees and participate in the 5000 doctoral scholarship program, and 3) PTKIS leaders build open lines of communication with their subordinates.